KORUPSI DAN DIALEKTIKA NILAI-NILAI SUFISTIK: Analisis Dampak Karakter Nasut Manusia Bagi Kehidupan - Sulaiman, Umar (Institut Agama Islam Negeri (IAIN) Metro, 2016)
This article wants to prove that a crime of corruption is very dominant and stretched in the institution of social life, economics, politics and the law is caused by excessive desire and the impulse nature of greedy owned human beings. In addition to the emergence of corrupt acts committed potential human beings due to chance and opportunity of power that is being performed by him. Corruption became a latent danger always haunts the human life, in which his action is a form of crime that ought to be wary. Therefore, he is seen as a social problem that can damage the joints structure of Government, and became the main obstacle in development. This paper also seeks to explore that that corruption is a crime that can act on tolerir and humane as the manifestation of the presence of potential lahut and nasut in man. When the potential human nasut more dominant, then the potential lahut experiencing fluctuations causing the onset of destructive anomalies that can undermine social institution, law and religion.